GoGlow Marker Pen Technology Enterpreneurship (ENT600) Technology Blueprint Report / Wan Mohd Zawir Wan Mokhtar - Wan Mokhtar, Wan Mohd Zawir (2020)
Our business is focusing in the production of glowing ink of marker pen. The main function of our marker pen product is the ink can be seen in the dark. Besides, the marker pen has two-sided features which allow consumers to write with the fine tip or broad tip of writing. The marker pen is well-designed using a low chemical material ink which is safe for consumers to use it as well safe to environment compared to the product of marker pen that currently available in the market which use a harmful chemical material for the ink of marker pen ad characterized by a very strong smell. Other than that, current marker pen does not provide the ink which can be seen in the dark. It would lead the users’ learning and teaching session being limited. For some view, although currently there is a glowing marker pen in the dark, it does not available in various colours of ink. Thus, this glowing marker pen can help to solve the common problems regarding current marker pen used in the market as it can fulfilled consumers’ need.